1881 Ill. Laws 71, § 4 - (:unkn) unknown (My University, 1881)
Prohibited the concealed carry or brandishing of any slung-shot, metallic knuckles, pistol, revolver, derringer, bowie knife, dirk, or other deadly weapon of like character. Violators punished by fine not less than twenty-five dollars nor more than two hundred dollars.
Keywords: BRANDISHING; CARRY - CONCEALED